Typification of two Gandoger’s names in Rhamnus (Rhamnaceae) - Ferrer-Gallego, P. Pablo; Rosselló, Josep A.; Sáez, Llorenç (Phytotaxa, 2020)
Gandoger’s names for Rhamnus bourgaeana and R. hispanorum (Rhamnaceae) are typified. A neotype is selected for R. bourgaeana, and a specimen preserved at M is designated as the lectotype of R. hispanorum.